Decision Support System Of Provision Of Assistance To Unable Students In SMP Pab 6 Lubuk Pakam With Analytical Hierarchy Process (AHP) Method - Desi Kristina Giawa; Miftahul Jannah (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
This research is based on the observations and experiences of researchers, that the provision of student assistance still does not cover all students who need it and supports the government's commitment to increase education participation rates in poor districts or cities and to remote areas. In addition, the expanded and enlarged assistance for underprivileged students will be able to suppress students from poor families/communities dropping out of school. Provision of Special Assistance for Underprivileged Students which is intended for students who are economically disadvantaged to pay school fees at SMP PAB 6 Lubuk Pakam. The number of criteria used to determine the provision of assistance makes it difficult to make decisions to assist underprivileged students. In addition, the assessment process is not always decided based on calculations that take a long time, so the determination of the provision of assistance to underprivileged students at SMP PAB 6 Lubuk Pakam still experiences many obstacles and delays. For this reason, a decision support system was built using a method that was appropriate to the existing problems. Therefore, the Analytical Hierarchy Process (AHP) method is used. This method is a framework for making effective decisions on problems by simplifying and accelerating the decision-making process by breaking the problem into its parts, arranging these parts or variables in a hierarchical arrangement, assigning numerical values to subjective judgments about the importance of each variable, and synthesizing them. these considerations determine which variable has the highest priority and act to influence the outcome of the situation. Decision Support System (DSS) with this AHP method can solve problems in determining assistance for underprivileged students. With the SPK assistance for underprivileged students so I can simplify and speed up decision making. SPK assistance for underprivileged students only provides recommendations for decisions to the school, for the next process, it is handed back to the school.